PERAN MAJELIS TA’LIM DALAM MEMBENTUK KECERDASAN EMOSIONAL ANAK (Penelitian di Majelis Ta’lim Nahjussalam Kecamatan Cijeungjing Kabupaten Ciamis) - Rahmayani, Nuri; Sahal, Yosep Farhan Dafik; Darifah, Udung Hari (Jurnal Penelitian Pendidikan Islam, 2015)
The purpose of this study was to determine the role of majlis taklim in shaping children's intelligence, which includes material and methods in majlis taklim, and its role in shaping children's emotional intelligence. Based on the research, the following conclusions were obtained: 1) The material studied in the Nahjussalam Muslim study council is the Qur'an, Iqra, Imla (writing Arabic without seeing), Kitab Al-Akhlaq li al-banan, tajwid, the books of Syafinah, the book of Tijan, Sulam Mutaufik, Kitab Ta'limulmuta'alim, Hadith Al-Arbain, Practices of prayer and reading, prayers, and memorization of short letters; 2) The method of implementing learning in the Nahjussalam Muslim ta'lim assembly is lecture, sorogan, question and answer and memorization; 3) The role of the majelis ta'lim Nahjussalam in shaping the emotional intelligence of children among them is an educational place that has an implicit message in every learning, instilling an attitude of believing in the existence of God and occult things, instilling a sense of responsibility to himself and others, to become a place of education religion, is a place to stay in touch, accommodate every activity of children's activities to channel the talents of children and adolescents that lead to positive pathways related to religion, become a spiritual recreation park, because its implementation is relaxed, as community empowerment through the development of economic and social potential, as a forum for fostering and developing religious life in order to form a society that is fearful of Allah, the nine media of delivering ideas that are beneficial to the development of the people and nation.